Final year medical students’ expectations for medical education on climate change and planetary health - a qualitative study - Flock, Charlotte; Boekels, Rebecca; Herrmann, Alina; Beig, Ilsa; Lamkemeyer, Lisa-Maria; Friederich, Hans-Christoph; Nikendei, Christoph; Bugaj, Till Johannes (Medical education online, 2025)
With the health impacts of climate change becoming increasingly evident, there is a pressing need to prepare and educate future physicians to address these challenges. This study therefore aims to explore in depth the perspectives of final-year medical students (FYMS) on the integration of Planetary Health Education (PHE) into medical curricula (i.e. content, methods, exams). Additionally, it seeks to understand how FYMS perceive the relevance of this topic to their future profession and their perceived responsibility. FYMS at the Heidelberg University Hospital were invited to participate in this qualitative interview study, resulting in 10 interviews conducted between December 2021 and March 2022. Using a semi-structured guide, students’ views on the role of climate change in their future profession and their preferences for integrating climate change into medical curricula were explored. Interviews were audio-recorded and transcribed verbatim. Data analysis followed a structuring qualitative content analysis approach according to Kuckartz, utilizing deductive and inductive methods. Coding was performed using MAXQDA24, with iterative revisions by the authors. Participating FYMS recognized the relevance of climate change to their future practice but expressed varying degrees of perceived responsibility in addressing it with patients, e.g. depending on their desired specialization. While often struggling to identify specific content for a PHE-curriculum, FYMS emphasized the wish for knowledge on health impacts of climate change, communication skills and interactive, practice-oriented teaching methods. FYMS also reported several reservations and perceived challenges, e.g. concerning the integration of basic climate science or the introduction of mandatory exams. This study provides unique insights into FYMS' perceptions of PHE, emphasizing the importance of integrating climate change and health topics into medical curricula and revealing perceived limitations. By aligning educational approaches with students’ preferences and especially their concerns, appealing curricula can ultimately foster a more climate-sensitive medical practice.